Midwives and the beginnings of gynaecology in Peru as seen in Ricardo Palma’s «Las brujas de Ica» - Siccha Malca, Mónica Milagros (2020)
This article will analyse the tradition «Las brujas de Ica» by the author Ricardo Palma. It aims to emphasise how midwives were perceived in ancient Peru and to understand how gynaecology emerged in our country, as well as its development and modernisation in the field of medicine.